Schiff Base Complexes for Lanthanide(III) Iodides - Arora, Kishor; Burman, Kiran (Asian Journal of Chemistry, 2010)
Some newly synthesized lanthanide(III) iodide complexes of Schiff bases having general composition LnL4I3 (Ln = La, Ce, Pr or Sm and L = 2N-(2-nitrobenzalidene)aminopyridine (2-NBAPy); 2N-(furfural)aminopyridine (FAPy); 2N-(3,4,5- trimethoxybenzalidene)aminopyridine (TMBAPY); and 2N- (4-chlorobenzalidene)aminopyridine (p-ClBAPy). These compounds were characterized on the basis of elemental analysis, molar conductance, molecular weight and spectral data. Coordination number six has been proposed for metal ion in these complexes.